Factors influencing cryoablation efficiacy in endometrial hyperplasia treatment - Żak, Halina; Baranowski, Włodzimierz (Menopause Review/Przegląd Menopauzalny, 2008)
The results of clinical efficacy of endometrial cryoablation in 50 women diagnosed with nonmalignant endometrial hyperplasia are described. The main aim of the study was to establish demographic, clinical and ultrasound factors determining the effectiveness of cryoablation in women with uterine bleeding due to nonmalignant hyperplastic endometrium. The ultimate aim of this work was to establish a specific algorithm for selection of a group of women with factors determining the best final therapeutic result. It was found that endometrial cryoablation is a very efficient method in women affected by uterine bleeding due to nonmalignant endometrial hyperplasia. Finally, the selection criteria for this procedure include non-obese women, having had menarche at 12 years old or later, having given birth no more than twice, and with endometrial thickness no more than 6.4 mm.